Herbage accumulation and canopy structure during stockpiling of Marandu, Piatã, Xaraés, and Paiaguás brachiariagrass cultivars - Santos, Manoel Eduardo Rozalino; Moraes, Lucas Santos de; Fernandes, Flávio Henrique de Oliveira; Carvalho, Bruno Humberto Rezende; Rocha, Gabriel de Oliveira; Andrade, Carlos Mauricio Soares de (Pesquisa Agropecuaria Brasileira, 2022)
The objective of this work was to compare herbage accumulation and canopy structural characteristics during the stockpiling period of the Marandu, Piatã, Xaraés, and Paiaguás cultivars of Urochloa brizantha. The experimental design was completely randomized, with three replicates. The experiment was repeated for two years (2017 and 2018), under mechanical cutting conditions, and the canopies were stockpiled for 90 days, from March to June. In the first year, forage mass was higher for the Xaraés and Paiaguás cultivars; however, in the second year, Xaraés showed a forage mass higher than that of the other cultivars. The number of vegetative tillers at the end of the stockpiling period was higher for Paiaguás, contrary to what was observed for number of reproductive tillers. The herbage accumulation rate was higher for the Paiaguás and Xaraés cultivars. The Paiaguás grass stands out for its high herbage accumulation rate during the stockpiling period and for its higher number of vegetative tillers and lower number of reproductive tillers than that of the other cultivars.